PENGUKURAN KEPUASAN PELANGGAN FACEBOOK MARKETPLACE DI KOTA BANDUNG DENGAN PENDEKATAN EXPECTANCY THEORY DAN E-SERVQUAL - Ahmad Abdilah Shodiqin; Yoki Oktorian Sukardi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study was conducted to answer three research questions, namely: (1) what is the current level of satisfaction among Facebook Marketplace users in Bandung; (2) what factors shape satisfaction according to EDT theory; and (3) what dimensions most significantly influence Facebook Marketplace user satisfaction according to e-servqual theory. This study applied a qualitative approach, in which data were collected through interviews, observations, and documentation. This study revealed the following proportions: (1) The current satisfaction level of Facebook Marketplace users in Bandung is determined by customer perceptions of the ease of use of the platform, trust, transaction security, and experience of interaction with sellers. (2) Facebook Marketplace user satisfaction is formed from Expectations, Perceived Performance, and Disconfirmation, and (3) Facebook Marketplace user satisfaction is influenced by the factors of Efficiency, System Availability, Fulfillment, and Privacy and Security. Finally, the dimensions of efficiency and fulfillment are the most dominant factors in influencing the level of customer satisfaction with Facebook Marketplace in Bandung..